Two new species of Lantana (Verbenaceae) from Brazil - Silva, Tânia Regina Dos Santos; Salimena, Fátima Regina Gonçalves; Lima, Carla Teixeira (Phytotaxa, 2017)
Two new species of Lantana are here described and illustrated. Lantana speciosa is endemic to the campos rupestres of the Espinhaço Range in Bahia and Minas Gerais, whilst Lantana restingensis is endemic to the restingas of the Atlantic forest in the state of Sergipe, northeastern Brazil. Comparative tables of morphologically similar and sympatric Lantana species are provided.